Pengaruh Latihan Gerak Aktif Kaki Dengan Teknik Open Kinetik Chain Exercise Terhadap Kekakuan Sendi Dan Aktivitas Fungsional Pada Lansia Dengan Osteoarthritis Dan Rheumatoid Di Panti Sosial Tresna Werdha Minaula Kendari - Asminarsih Zainal Prio; Sitti Rachmi Misbah; Fitri Wijayati (Jurnal Keperawatan, 2019)
Osteoarthritis and rheumatoid arthritis was a common musculoskeletal alteration in the world that caused impairment and disability in elderly. It was manifest by pain, inflexibility joint, and decreased of fungsional activity. There was not specialy exercise for elderly with inflexibility joint and functional activities caused by osteoarthritis and rheumatoid at the Minaula Social Institution of Elderly at Kendari.This researches aims to examine the effect of foot exercise with open kinetic chain methods to inflexibility joint and functional activities caused by osteoarthritis and rheumatoid at the Minaula Social Institution of Elderly at Kendari. The method used in this research was quasi experimental using pretest and posttest with control group design. Data collections was conducted by simple random sampling to reach 60 participant 930 in intervention group and 30 in control group). The result showed that mean of pain level of intervention group was decreased as 4,83 after foot exercise with open kinetic chain methods (mean before 5,80, mean after 0,97). The conclution of this research there was an effectiveness of foot exercise with open kinetic chain methods to inflexibility joint caused by osteoarthritis and rheumatoid at Minaula Social Institution of Elderly at Kendari 2016 (p value = 0,000), and there was an effectiveness of foot exercise with open kinetic chain methods to functional activities caused by osteoarthritis and rheumatoid at Minaula Social Institution of Elderly at Kendari 2016 (p value = 0,000) This research implied that foot exercise with open kinetic chain methods can be consider as one of nursing competencies and applied as a nursing intervention to inflexibility joint and functional activitiescaused by osteoarthritis and rheumatoid. It is recommended to make a book of osteoarthritis management at Social Institution of elderly or at home and it is necessary to simulation of foot exercise with open kinetic chain methods to people with osteoarthritis and rheumatoid by health professional.